Critical Thinking Skills: Comparative Assessment of Further Mathematics and Non-Further Mathematics Students in Public and Private Schools - Etuk-Iren, Olubunmi Adejoke; Bakre, Omolara Fatimah; Lawal, Ruth Folake (Brillo Journal, 2024)
Critical thinking skills, essential for daily progress and academic success, are rarely studied in relation to Further Mathematics. This study compared the critical thinking skills of further mathematics and non-further mathematics students in Alimosho, Lagos, Nigeria. A total of 310 participants, including 153 further mathematics and 157 non-further mathematics students, were purposively selected from public and private secondary schools. Data were collected using a valid and reliable questionnaire (r=0.82) and analyzed using descriptive and inferential statistics, including frequency, mean, standard deviation, and t-test at a 0.05 significance level. The results revealed a significant difference in critical thinking skills between further mathematics and non-further mathematics students in public secondary schools. Similarly, a significant difference was found in the critical thinking skills of public and private school students, regardless of whether they studied mathematics. No significant difference was observed in the critical thinking skills of students taking further mathematics compared to those who did not, across both types of institutions. The study recommended that mathematics teachers focus on fostering critical thinking skills beyond problem-solving in further mathematics to support students' overall development.